Phenomenon of improper attitude in Szczecin sport during the years 1945–1956 - Stefanik, Ryszard (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
This paper presents historical, social and political conditions of development of sport in Szczecin Voivodship during the years 1945–1956. It draws attention to the occurrence of improper phenomenon including demoralization of this environment starting with aggressive, hooligan attitudes to the corruption symptoms. The subject of this analysis is also the policy of the authorities towards the society and its influence on forming of ethics/morality of the sports world.